A spatio-temporal multiplexing multi-view display using a lenticular lens and a beam steering screen - Zhang, Xiangyu (2019)
A new type of spatio-temporal multiplexing multi-view three-dimensional (3D) display with horizontal motion parallax has been developed. The proposed 3D display system comprises: a fast liquid-crystal-display (LCD), a lenticular lens and a beam steering screen. The lenticular lens is customized for the LCD screen so as to project the display image into different directions. The beam steering screen is fabricated by using two layers of twisted-nematic (TN) LC cells with micro-prism-array(MPA) substrates, and multiple polarization statues can be produced by regulating the biasing voltages on the steering screen. Image light beam from the LCD screen is firstly split by the lenticular lens, and then further deflected to desired directions by the steering screen. Thus, the proposed method implements temporal multiplexing onto common spatial multiplexing multi-view displays, and dense viewing zones are created horizontally in space. A complete prototype based on this technology has been developed, and the proof of concept has been verified by experimental results.